Legal Politics of Privacy Protection against Doxing Cases on Social Media - Syahrial, Syahrial; Barthos, Megawati (International Journal of Social Service and Research, 2025)
Doxing refers to the act of spreading a person's private information into the public digital sphere without consent, potentially leading to psychological distress, damage to reputation, and even physical threats. This issue has intensified with the rise of social media usage and inadequate privacy protections within Indonesia's digital environment. The legal framework governing privacy protection must be reoriented to address this challenge more comprehensively and adaptively. This study aims to explore how Indonesian laws currently regulate doxing and evaluate the effectiveness of the existing legal framework in safeguarding the privacy and self-esteem of victims. Employing a normative juridical method with a legislative approach, this research is also supported by conceptual analysis of legal doctrines. The study finds that legal protections against doxing are fragmented across various regulations, such as the ITE Law, the Personal Data Protection Law, and ministerial regulations concerning electronic systems, yet there is no explicit law that specifically addresses doxing. As a result, law enforcement often struggles to classify doxing as a specific criminal offense. The legal politics of Indonesia have been reactive, failing to meet the comprehensive needs of victims, both in terms of law enforcement and dignity restoration. This paper concludes by advocating for a more progressive, participatory, and victim-oriented legal framework, with explicit regulations on doxing that incorporate human rights-based personal data protection and mechanisms to support victims.